PERAN CITRA MEREK SEBAGAI MEDIASI PENGARUH CELEBRITY ENDORSER DAN VIRAL MARKETING TERHADAP MOTIVASI KEPUTUSAN PEMBELIAN OREO X BLACKPINK - Rahmawati, Yessica Gustya; Suryaningsih, Ika Barokah; Musmedi, Didik Pudjo (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2023)
This research aims to examine the role of brand image as a mediator variable in the influence of celebrity endorser and viral marketing on decision motivation to purchase Oreo X Blackpink. This research was designed using explanatory research. Respondents were Blackpink fans who use social media Twitter in Indonesia. The sample used was 112 respondents with purposive sampling as the sampling method. Path analysis is a data analysis method that was used in this research. The results showed that: (1) Celebrity endorser has a significant and positive effect on brand image; (2) Viral marketing has a significant and positive effect on brand image; (3) Celebrity endorser has a significant and positive effect on purchase decision motivation; (4) Viral marketing has a significant and positive effect on purchase decision motivation; (5) Brand image has a significant and positive effect on purchase decision motivation; (6) Celebrity endorser has a significant and positive effect on purchase decision motivation through brand image; (7) Viral marketing has a significant and positive effect on purchase decision motivation through brand image.